FAKTOR YANG MEMPENGARUHI HASIL BELAJAR PESERTA DIDIK KELAS VIII DI SMP N I LEMBAH MELINTANG - YASRIZAL, YASRIZAL; Kasih, Fitria; Zulkifli, Zulkifli (Bimbingan dan Konseling, 2013)
ABSTRACTThe problem of this research was the influential factor on the learning outcome of students. This research was conducted at SMPN 1 Lembah Malintang. This research aim to know internal and external factors which influence the learning outcome. This research was a descriptive study. The population of this research was all students at SMPN 1 of Lembah Melintang. Technique of taking sample was conducted by proportional random sampling where the drawing of sample was done randomly. As for the population of this research was 241 students of class VIII, after doing the drawing sample randomly, the amount of sample was 40 students. The data of this research was obtained by using questionnaire of the research. The data that has been obtained and then to be analyzed by using descriptive analysis. From the data analysis was conducted can be concluded that the influential factor of studentsâ learning outcome at SMPN 1 Lembah Melintang, those are 73.91% with a lot criteria. From the influential factor uncovered when seeing from the aspect of school regulation was dominant to influence the studentsâ learning outcome, those are 89,92% they influence the studentsâ learning outcome by abundant criteria.